Nanostructure-Based Solid-State Energy Storage through Hydrogen Trapping in Batteries Using Materials Modelling Technique - Mollaamin, Fatemeh (LIDSEN Publishing Inc, 2024)
A comprehensive investigation on hydrogen grabbing by SiO-GeO was carried out, including DFT computations at the CAM-B3LYP-D3/6-311+G (d,p) level of theory. The data shows that if silicon elements are replaced by germanium, the H-grabbing energy will be ameliorated. Electromagnetic and thermodynamic properties of SiO, GeO, and SiO-GeO nanoclusters have been evaluated. The hypothesis of the hydrogen adsorption phenomenon was confirmed by density distributions of PDOS and LOL for hydrated nanoclusters of H-SiO, H-GeO, and H-SiO-GeO-H. The fluctuation in charge density values demonstrates that the electronic densities were mainly located in the boundary of adsorbate/adsorbent atoms during the adsorption status. The advantages of germanium over silicon include its higher electron and hole mobility, allowing germanium devices to operate at higher frequencies than silicon devices. Therefore, by combining SiO and GeO, it can be concluded that the SiO-GeO nanocluster might be an appropriate candidate for hydrogen storage in transistors.